Wild species of vaccinium composition, nutritional value and utilization - Mirghani, Mohamed Elwathig Saeed; Daoud, Jamal Ibrahim; Mohamed Elnour, Ahmed Adam (Springer Nature Switzerland AG. Part of Springer Nature., 2019)
There are still, in many parts of the globe, some edible fruit collects from the wild for human feeding and other uses. These fruits are utilised either in their raw nature or after some form of processing. One of these wild fruits are Vaccinium species such as Vaccinium myrtoides (Blume) Miq., Vaccinium cylindraceum, Vaccinium padifolium, Vaccinium corymbosum, Vaccinium myrtillus and others from the plant family Ericaceae. The term wild infers non-cultivated plants found in plantation felids or the forest. The species Vaccinium myrtoides and the others are small trees (shrubs) that are well known in Southeast Asian countries such as Philippines, Indonesia and other neighbouring islands. The plants classified as wild growing shrubs. However, the locals have made it be fully utilized in some areas as the wood that are used in grafting utensils and cutleries, or as fuel and fruits. The small-sized berry-like fruits with an average diameter of about 4–5 mm turn black when ripe. They have a delicious flavour that makes it edible and used in the making of other delicacies such as tart and pies to add flavour and as preservatives as well. A few published researches were done on Vaccinium myrtoides showing that it is still used in folkloric medicine. Leaves and fruits extracts showed strong antioxidant activity when tested in-vitro using DPPH (2, 2-diphenyl-1-picrylhydrazyl) free radical scavenging activity as part of a preliminary phytochemical screening for V. myrtoides. The study revealed that the antioxidant activity is due to the presence of flavonoids and other phenolic compounds in the plant leaves and fruit extracts.